A fog computing model for pervasive connected healthcare in smart environments. (25th June 2019) - Moore, Philip; Pham, Hai Van
Healthcare provision faces many demand and resource challenges. Addressing these challenges requires effective patient management which may be achieved using autonomic health monitoring systems. However, such monitoring has been limited to 'smart-homes'; we propose extending the 'smart-home' to a wider 'smart-environment' which conflates 'smart-homes' with the 'smart-city' (in an interconnected environment) based on the fog computing paradigm. We introduce our low latency fog computing model which is designed to enable 'real-time' patient monitoring with situational awareness, pervasive consciousness, and related data analytic solutions. Illustrative scenarios are presented along with a 'real-world' example of a proposed 'smart-environment'. Context-awareness and decision support are considered with a proposed implementation strategy and a 'real-world' case study in the healthcare domain. While the proposed fog model and implementation strategy is predicated on healthcare domain, the proposed fog computing model will generalise to other medical conditions and domains of interest.